Microstructural Evolution and Mechanical Properties of 2D–SiCf/SiC and Hastelloy N Joints Using 82.5Au–17.5Ni Brazing Filler1 . Issue 11 (6th September 2016) - Liu, Min; Yang, Xinmei; Zhou, Haijun; Gao, Yantao; Xia, Huihao; Huai, Ping; Zhou, Xingtai; Lu, Yanling
Abstract : In this paper, SiC fiber reinforced SiC composite (SiCf /SiC) is joined to Hastelloy N alloy using 82.5Au–17.5Ni (wt%) foil as brazing filler. The microstructural evolution of the joints is investigated using scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), X‐ray diffraction (XRD), and Raman spectroscopy. The shear strengths of the joints are tested by the mechanical testing machine. The results show the formation of nanocrystalline graphites, Ni2 Si layer, and Ni31 Si12 phases. With increasing temperature, Ni2 Si is transformed gradually into Ni31 Si12 . The shear strength reaches a maximum value of 24.5 MPa when the joint is brazed at 1 000 °C for 30 min. Abstract : SiCf /SiC composites are joined to Hastelloy N alloys using 82.5Au–17.5Ni (wt%) foil as brazing filler. The brazing temperature and holding time have a great influence on the microstructure and shear strength of the joints. Nanocrystalline graphite, Ni2 Si, and Ni31 Si12 are formed in brazed seams.